Tax Illusion and the Labor Supply of Married Women - Rosen, Harvey S. (The Review of Economics and Statistics, 1976)
THE economic and demographic determinants of the labor force behavior of married females have been studied intensively.' Many of the important variables have now been isolated: education, age, income of husband, number of children, etc. However, as will be discussed below, the existing literature pays insufficient attention to the fact that U.S. income tax laws have placed a large burden on the earnings of married women. When a married couple chooses to enjoy the tax advantages of filing jointly, the first dollar earned by the wife is in effect taxed at the same marginal rate as the last dollar earned by the husband.2 The purpose of this paper is to present some empirical results on the impact of tax rates on the labor supply of married women. Explicit attention is focused on the extent to which individuals react to net rather than gross wages. The evidence strongly supports the view that it is the net wage that matters in the hours of work decision. Section I briefly discusses how taxes have been treated traditionally in the analysis of labor supply. Section II presents a model for examining the impact of taxes on labor supply, and section III contains the results of an empirical test of this model. A concluding section discusses work in progress which will refine and extend the results of this paper.